Case Report: Novel JAG1 gene mutations in two infants with alagille syndrome characterized by cholestasis - Han, Yijiang; Zhu, Kun; Wu, Hao; Chen, Baohai; Hu, Shuqi; Lai, Dengming; Tou, Jinfa (Frontiers in Pediatrics, 2022)
Background: Infants with Alagille syndrome (ALGS) need to be promptly differentiated from biliary atresia (BA) at an early stage. ALGS is an autosomal, dominant, multisystem disorder with variable phenotypic penetrance caused by heterozygous mutations in JAG1 or NOTCH2, which encode the Notch signaling pathway. Case presentation: We report two cases, both with cholestatic jaundice as the main manifestation, in which BA was excluded and finally diagnosed as ALGS based on characteristic facial features, serological tests, imaging, laparoscopic cholangiography, pathology and genetic findings. Both cases are novel mutant genes on chromosome 20 that have not been reported in the literature. The mutation in patient 1 was a novel heterozygous nonsense mutation (NM_000214 exon20, c.2419G＞T, p.E807Ter) , which was a spontaneous mutation. Followed up to 1 year and 6 months, the symptoms resolved with ursodeoxycholic acid and cholestyramine, and the jaundice has now subsided. Patient 2 was a novel heterozygous frameshift mutation (NM_000214 exon19, c.2367-2368dupTC, p.P790Lfs*31), which was inherited from his mother. This patient was followed up to 9 months and is currently awaiting liver transplantation. Conclusion: Both cholestatic infants reported combined to exclude BA, avoid Kasai portoenterostomy (KPE), and definitively diagnose ALGS. Broadening the spectrum of JAG1 gene mutations.